Evaluation of the Diesse Cube 30 touch erythrocyte sedimentation method in comparison with Alifax test 1 and the manual Westergren gold standard method. (3rd May 2021) - Pieri, Massimo; Pignalosa, Stefano; Perrone, Marco Alfonso; Russo, Carmelo; Noce, Gianluca; Perrone, Andrea; Terrinoni, Alessandro; Massoud, Renato; Bernardini, Sergio
Abstract: The erythrocyte sedimentation rate (ESR) is a traditional nonspecific laboratory test used for the assessment of inflammation. Even if its usefulness is nowadays being largely debated, it is still considered a valuable laboratory test in selected clinical conditions, such as rheumatoid diseases, orthopedic infections and Hodgkin's lymphoma, and it can be used for the infectious, inflammatory, malignancies, and autoimmune diseases follow-up. The introduction of new methodologies on semi-automated and automated analyzers started about four decades ago and opened a new era of ESR analysis characterized by shorter assay time, use of (EDTA) undiluted blood, that increases sample stability and allows using a single sample for also other hematologic tests, and greater safety for laboratory personnel. In this context, the aim of this study was to evaluate the performances of new device Diesse Cube 30 touch, comparing it with Alifax Test 1 and with the gold standard Westergren method. The new Diesse Cube 30 touch for determination of the ESR shows a good correlation with the manual Westergren gold standard method in a shorter time, and in a standardized way, since all the phases of the test are automatized. The Diesse Cube 30 touch respect the manual gold standard method, displayed a small bias to confirm that the new automated test system tended to have a small bias for ESR values (mean positive bias +0.2 mm/h). The findings of the present study show that the Diesse Cube 30 touch Westergren-based method can be a valid alternative in laboratory analysis for the determination of ESR.